The Effect of Aging on Quality of Life in Acromegaly Patients Under Treatment - Yamamoto, Naoki; Urai, Shin; Fukuoka, Hidenori; Yamamoto, Masaaki; Yoshida, Kenichi; Suzuki, Masaki; Shichi, Hiroki; Fujita, Yasunori; Kanie, Keitaro; Iguchi, Genzo; Takahashi, Yutaka; Ogawa, Wataru (Frontiers in Endocrinology, 2022)
Context: With the increasing number of older patients with acromegaly, it is important to understand the effects of aging on the quality of life (QoL) in acromegaly. Objective: To investigate the factors associated with the QoL of older acromegaly patients. Design: This was a single-center, retrospective, cross-sectional study conducted between 2014 and 2019. Methods: Among 90 acromegaly patients at Kobe University Hospital, 74 who had completed the QoL evaluation under treatment were enrolled (age = 62.0 [50.7–70.0], female 52%). SF-36 and the AcroQoL questionnaire were used to quantify QoL. The patients were divided into two groups: the young and middle-aged group, aged <65 years (51.0 [46.0–59.2], n =42), and the older group, aged ≥65 years (70.5 [69.0–73.0], n =32). The factors associated with the QoL scores were analyzed using univariate and multivariate regression analyses. Results: The scores for the physical component summary of SF-36 were negatively associated with age (P <0.01), while those for the mental or role/social component summary were positively associated (P <0.01, P =0.03, respectively). In contrast, AcroQoL scores were not associated with age. However, the different factors were associated with lower AcroQoL scores; arthropathy and higher BMI in the older group (P <0.01, and P =0.01, respectively), and treatment modalities and size of pituitary tumor in the young and middle-aged group (P <0.01, P =0.04, respectively). Replacement of hydrocortisone was commonly associated both in young and middle-aged group (P =0.04), and in older group (P =0.02). Conclusion: We showed that the factors associated with impaired QoL differed in the young and middle-aged, and older patients with acromegaly. In older patients, arthropathy and higher BMI were associated with poor QoL. These suggest the importance of early diagnosis and appropriate treatment in preventing arthropathy in acromegaly.